Analisis Strategi Pemungutan Pajak Air Tanah Dalam Rangka Meningkatkan Penerimaan Pajak Daerah Kabupaten Buton Utara Tahun 2018-2020 - Hamka, Waode Helvi Mei; Permatasari, Mira (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to evaluate the methods of groundwater tax collection implemented to enhance local revenue in North Buton Regency during the period of 2018-2020. Additionally, it seeks to identify factors influencing this process, including both impediments and facilitators. The research methodology employed is descriptive qualitative, with primary data collected through interviews and secondary data comprising targets and realizations of groundwater tax revenues. The findings indicate that the implementation of the groundwater tax collection strategy to increase local tax revenue in North Buton Regency has not been optimal, due to several obstacles such as the insufficiency of human resources, inadequate infrastructure, and insufficient oversight, among other barriers.